Factors Influencing the Giving of Early MP ASI to Infants 0-6 Months in the Work Area of Campaka Puskesmas, Purwakarta District - Fitri Nurfaridah; Lia Idealistiana (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: This study was to determine the factors of early complementary breastfeeding in infants 0-6 months in the Working Area of ​​the Community Health Center, Campaka District, Kab. Purwakarta Year 2022. Method: The research design is analytic descriptive with a cross sectional approach. The sample of this study were all mothers who had babies aged (0-6) months who were in the working area of ​​the Puskesmas, Campaka District, Kab. Purwakarta, amounting to 30 people. This study uses univariate and bivariate analysis. Result: The results of the univariate analysis of this study showed that of the 30 respondents, almost half (53%) had a supportive attitude, more than half (60%) worked, almost some (40%) had supportive husbands and more than half provided early MP ASI. The results of the bivariate analysis obtained attitudes with a value of p = 0.003 ≤ α = 0.05, thus indicating that attitude factors have an influence in giving MP ASI to infants aged 0-6 months at the Campaka District Health Center, Kab. Purwakarta in 2022. Conclusion: The results of this study indicate that the attitude variable is most related to early complementary breastfeeding to infants aged 0-6 months at the Campaka District Health Center, Kab. Purwakarta in 2022. It is hoped that the puskesmas will increase the dissemination of information through outreach to the community through the role of cadres in order to increase knowledge about the importance of exclusive breastfeeding.